Inferring ecological strategies of Psenopsis spp. (Teleostei: Centrolophidae) inhabiting Indian waters from morphological features. Issue 3 (21st April 2022) - Kumar, K. V. Aneesh; Rajeeshkumar, M. P.; Hashim, M.; Deepa, K. P.; Otero-Ferrer, J. L.; Saravanane, N.; Thomas, Sujitha; Bineesh, K. K.; Tuset, V. M.
ABSTRACT: Morphology of the fish and otoliths are popularly used in the discrimination of species/stocks/populations and also to gather meaningful conclusions about their ecology. This approach is useful to enhance our understanding of the relationship between form and function in fishes when a direct assessment is impossible. Inter-species variation was analysed using geometric morphometric analysis for fish body shape, while morphometry and wavelet functions for sagittae morphology. A clear ecomorphological pattern in the body, as well as otolith shape, is evident among species as deeper inhabiting species possess a deeper body with oblong otoliths compared with shallower species that possess a more streamlined body with fusiform otoliths. We also observed that deeper species ( P. obscura ) possess bigger eyes for the optimum use of available light and bigger otoliths with higher otolith sensory area and otolith area ratio (S:O) for better sound reception capacities. Our hypothesis supports that the differences in fish morphological as well as sensorial traits (otoliths), which are closely related to their locomotion, foraging pattern and depth of habitation, lead to trophic segregation which in turn encourages their coexistence. This is the first work that discusses the relationship between body shape, otolith morphometry and morphology in deep-sea fishes and their ecomorphological interpretations. http://zoobank.org/lsid:zoobank.org:pub:663DD393-80B0-407D-907C-51E3F33ECCFB